Genetic and Epidemiological Study of Adult Ataxia and Spastic Paraplegia in Eastern Quebec. (5th September 2021) - Haj Salem, Ikhlass; Beaudin, Marie; Stumpf, Monica; Estiar, Mehrdad A.; Côté, Pierre-Olivier; Brunet, Francis; Gamache, Pierre-Luc; Rouleau, Guy A.; Mourabit-Amari, Karim; Gan-Or, Ziv; Dupré, Nicolas
ABSTRACT: Objective: To estimate the minimum prevalence of adult hereditary ataxias (HA) and spastic paraplegias (HSP) in Eastern Quebec and to evaluate the proportion of associated mutations in identified genes. Methods: We conducted a descriptive cross-sectional study of patients who met clinical criteria for the diagnosis of HA ( n = 241) and HSP ( n = 115) in the East of the Quebec province between January 2007 and July 2019. The primary outcome was the prevalence per 100, 000 persons with a 95% confidence interval (CI). The secondary outcome was the frequency of mutations identified by targeted next-generation sequencing (NGS) approach. Minimum carrier frequency for identified variants was calculated based on allele frequency values and the Hardy–Weinberg (HW) equation. Results: The minimum prevalence of HA in Eastern Quebec was estimated at 6.47/100 000 [95% CI; 6.44–6.51]; divided into 3.73/100 000 for autosomal recessive (AR) ataxias and 2.67/100 000 for autosomal dominant (AD) ataxias. The minimum prevalence of HSP was 4.17/100 000 [95% CI; 4.14–4.2]; with 2.05/100 000 for AD-HSP and 2.12/100 000 for AR-HSP. In total, 52.4% of patients had a confirmed genetic diagnosis. AR cerebellar ataxia type 1 (2.67/100 000) and AD spastic paraplegia SPG4 (1.18/100 000) were the most prevalent disorders identified. Mutations were identified in 23 genes and molecular alterations in 7 trinucleotides repeats expansion; the most common mutations were c.15705–12 A > G in SYNE1 and c.1529C > T (p.A510V) in SPG7 . Conclusions: We described the minimum prevalence of genetically defined adult HA and HSP in Eastern Quebec. This study provides a framework for international comparisons and service planning.